Understanding the Self-Harming Behavior of Filipino Male Detainees (32–58 Years Old): A Descriptive Phenomenology - Clemente-Faustino, Julie Ann R. (International journal of offender therapy and comparative criminology, 2024)
Self-harming behavior (SHB) has become a significant health issue among several populations, including adolescents, traumatized individuals, and persons deprived of liberty. Undoubtedly, incarceration takes a toll on inmates’ mental health due to several stressful experiences while in custody. These taxing events make them vulnerable to maladaptive coping strategies, such as SHB. To date, many studies on this behavior have focused on high-income countries. Research has not explored much on this behavior among inmates in developing countries such as the Philippines. This phenomenological inquiry aims to characterize the experiences of select older male Filipino detainees engaged in SHB. Through vertical and horizontal analyses of the narratives shared, this study conceptualized the Self-Harming Behavior of Older Filipino Detainees as Tension and Compression. This model shows the forces that either pull or push the detainees to engage in self-injurious acts. Specifically, the seven themes surfaced: life dispositions, jail ecology, emotional baggage, physically and chemically-induced self-harming behavior, consequences, coping strategies, and cognizance. Findings from this inquiry may necessitate the provision of adequate and comprehensive prevention and intervention services for the self-harmers in jail, which are geared toward implementing a thorough psychological evaluation and promoting sound psychological well-being.